Six years - Coben, Harlan, 1962- (New York : Dutton, 2013)
"Six years have passed since Jake Sanders watched Natalie, the love of his life, marry another man. But six years haven't come close to extinguishing his feelings, and when Jake comes across Todd's obituary, he can't keep himself away from the funeral. There he gets the glimpse of Todd's wife he's hoping for . . . but she is not Natalie"-- Jacket.
Keywords: Missing persons -- Fiction; Unrequited love -- Fiction; Mystery fiction; Suspense fiction